Persuasive Communication of Wilayatul Hisbah in Sharia Enforcement in Aceh Besar - Rahmat Nazar (Pusaka Cendekia Indonesia Foundation, 2026)
This study examines persuasive communication used by Wilayatul Hisbah (WH) in supporting the enforcement of Islamic sharia regulations in Aceh Besar, Indonesia. Using a qualitative descriptive case-study approach, the research draws on interviews, field observation, and institutional documents concerning WH communication and enforcement activities. The analysis identifies three interrelated modes of persuasion: educational communication that translates legal and religious norms into accessible advice and socialization; dialogic communication that creates space for two-way explanation and response; and humanistic communication that emphasizes empathy, dignity, and proportionality. These modes are combined with preventive monitoring and formal enforcement rather than replacing them. The findings suggest that persuasive interaction can strengthen legal understanding, reduce interactional resistance, and create conditions for voluntary compliance. However, the available qualitative evidence does not establish a causal decline in violation rates. The study contributes by interpreting WH communication through persuasion and procedural-legitimacy perspectives and by showing that effective sharia enforcement depends not only on regulatory authority but also on message design, communicator credibility, respectful treatment, and community legal literacy. Penelitian ini mengkaji komunikasi persuasif yang digunakan Wilayatul Hisbah (WH) dalam mendukung penegakan regulasi syariat Islam di Kabupaten Aceh Besar. Penelitian menggunakan pendekatan kualitatif deskriptif dengan desain studi kasus melalui wawancara, observasi lapangan, dan telaah dokumen kelembagaan terkait aktivitas komunikasi dan penegakan WH. Analisis menemukan tiga pola persuasi yang saling berkaitan, yaitu komunikasi edukatif yang menerjemahkan norma hukum dan agama ke dalam nasihat serta sosialisasi yang mudah dipahami; komunikasi dialogis yang membuka ruang penjelasan dan tanggapan dua arah; serta komunikasi humanis yang menekankan empati, martabat, dan proporsionalitas. Ketiga pola tersebut dipadukan dengan langkah preventif dan penegakan formal, bukan untuk menggantikannya. Temuan menunjukkan bahwa interaksi persuasif berpotensi memperkuat pemahaman hukum, mengurangi resistensi interaksional, dan menciptakan kondisi bagi kepatuhan sukarela. Namun, bukti kualitatif yang tersedia belum cukup untuk membuktikan penurunan angka pelanggaran secara kausal. Penelitian menegaskan pentingnya desain pesan, kredibilitas komunikator, perlakuan yang menghormati masyarakat, dan literasi hukum dalam penegakan syariat.